Assessment of immunoglobulin concentrates on thrombogenic activity by thrombin generation assay, prekallikrein activator assay, and size‐exclusion chromatography. Issue 2 (17th June 2013) - Seifner, Alexandra; Beck, Gerhard; Bayer, Patrick; Eichmeir, Stephanie; Lackner, Friedrich; Rögelsperger, Olga; Weber, Katharina; Wollein, Gabriele
<x xml:space="preserve">Abstract</x> Background Immunoglobulin G (IgG) concentrates have recently been found to be contaminated with procoagulant impurities causing thromboembolic events (TEEs) in vivo. In this study the question was raised whether a thrombin generation assay (TGA) will be able to characterize IgG samples from the Austrian market with regard to their thrombogenic potential. Study Design and Methods A total of 44 IgG concentrates have been assayed by TGA employing pooled normal plasma and Factor (F)XI‐deficient plasma (FXIdp). Furthermore, the prekallikrein activator assay including determination of blank values, size‐exclusion chromatography, and further test systems required for batch release testing of IgG concentrates according to the European Pharmacopeia (Pharm. Eur.) were carried out. Results All samples complied with acceptance criteria stated in the Plarm. Eur. and/or prescribed by the marketing approval. One intravenous immunoglobulin (IVIG) involved in TEEs exceeded a threshold level of 350 nmol peak thrombin, which was not exceeded after change of manufacture and by all the other IVIGs tested. Two hyperimmune globulins revealed elevated peak thrombin levels of up to 810 nmol in FXI and up to 285 nmol in FXIdp. Conclusion The study indicates that the TGA is able to reliably predict procoagulant activities probably associated with the presence of FXIa and potential thrombogenicity. Comparison of thrombin generation with product‐specific acceptance criteria as well as variables from other test systems as amidolytic activity and molecular size can help to monitor IgG quality and manufacturing changes with regard to thrombogenicity.